Natural Killer Cells in Antibody Independent and Antibody Dependent HIV Control - Bernard, Nicole F.; Kant, Sanket; Kiani, Zahra; Tremblay, Cécile; Dupuy, Franck P. (Frontiers in Immunology, 2022)
Infection with the human immunodeficiency virus (HIV), when left untreated, typically leads to disease progression towards acquired immunodeficiency syndrome. Some people living with HIV (PLWH) control their virus to levels below the limit of detection of standard viral load assays, without treatment. As such, they represent examples of a functional HIV cure. These individuals, called Elite Controllers (ECs), are rare, making up <1% of PLWH. Genome wide association studies mapped genes in the major histocompatibility complex (MHC) class I region as important in HIV control. ECs have potent virus specific CD8+ T cell responses often restricted by protective MHC class I antigens. Natural Killer (NK) cells are innate immune cells whose activation state depends on the integration of activating and inhibitory signals arising from cell surface receptors interacting with their ligands on neighboring cells. Inhibitory NK cell receptors also use a subset of MHC class I antigens as ligands. This interaction educates NK cells, priming them to respond to HIV infected cell with reduced MHC class I antigen expression levels. NK cells can also be activated through the crosslinking of the activating NK cell receptor, CD16, which binds the fragment crystallizable portion of immunoglobulin G. This mode of activation confers NK cells with specificity to HIV infected cells when the antigen binding portion of CD16 bound immunoglobulin G recognizes HIV Envelope on infected cells. Here, we will review the role of NK cells in antibody independent and antibody dependent HIV control.